2014
DOI: 10.1245/s10434-014-3823-2
|View full text |Cite
|
Sign up to set email alerts
|

Chen’s U-Suture Technique for End-to-End Invaginated Pancreaticojejunostomy Following Pancreaticoduodenectomy

Abstract: This new surgical technique (Chen's U-stitch), which involves an end-to-end invaginated pancreaticojejunostomy with two to four transpancreatic transverse U-sutures, provides excellent outcomes at reducing the incidence of POPF after PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 21 publications
0
23
0
3
Order By: Relevance
“…Therefore, a reliable way to better place the tube into the main pancreatic duct and carefully x this structure is needed (21). Hence many surgical procedures have been used in the management of the pancreatic remnant including pancreaticojejunostomy, pancreaticogastrostomy and other new PJ technology (16,17). Besides, recent studies found that the smear positivity of drainage uid on POD 3 was one of the independent risk factors for POPF (22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a reliable way to better place the tube into the main pancreatic duct and carefully x this structure is needed (21). Hence many surgical procedures have been used in the management of the pancreatic remnant including pancreaticojejunostomy, pancreaticogastrostomy and other new PJ technology (16,17). Besides, recent studies found that the smear positivity of drainage uid on POD 3 was one of the independent risk factors for POPF (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Well recognized risk factors related to POPF include gender, diabetes, BMI, pancreaticojejunal anastomosis technique, the diameter of the pancreaticduct and pancreatic texture (9) . As pancreaticojejunostomy(PJ) is the most crucial step, numerous surgical groups have investigated several methods to build a stable PJ for reducing the incidence of POPF (2,5,10), including pancreaticogastrostomy(11), duct-to-mucosa anastomosis(12), pancreatic duct occlusion, the use of biologic adhesive (13-15), Chen's U-stitch approach (16) and end-to-side suspender PJ (17). Here, in our institution, we studied a novel anastomosis technique where we use the half purse-string suture on the basis of two-layer duct-to-mucosa pancreaticojejunostomy technique, which effectively invaginated the pancreas into the jejunum in addition to allowing a duct-to-mucosa anastomosis.…”
Section: Introductionmentioning
confidence: 99%
“…Учитывая существующие методики транспаренхиматозных швов, мы уделили основное внимание задней стенке соустья [18,19,45]. Непосредственная близость к сосудам делает формирование скопления sinister fluid в этой области угрожающим в отношении аррозии магистральных артерий.…”
Section: Discussionunclassified
“…[32] . (a) 胆管全插入式胆管-空肠Roux-en-Y吻合; (b) 胆管前壁插入式Roux-en-Y吻合术 术改进 , 但胰漏发生率仍然高达13.1%~20.3% [34~36] , 本中心建立了一种新的U型胰肠套入式吻合法(陈氏 U型缝合法)可明显降低胰漏发生率 [37,38] . 缝合技术 要点(图8): Surgery is the most effective and preferred treatment for hepato-pancreato-biliary (HPB) tumors.…”
Section: 小 范 围 肝 切 除 治 疗 肝 门 部 胆 管 癌 的 新 理念unclassified